Frozen section allows more accurate management in suspected ovarian malignancy in young women - Nuranna, Laila; Loho, Ditha Adriana; Hia, Christin Wigin (Majalah Obstetri & Ginekologi, 2020)
Objectives: To present three cases of young women with suspected ovarian malignancy with the aim to evaluate the role of intraoperative frozen section in suspected malignant ovarian neoplasms in women with young age. Case Report: Mrs. M, 25 years old, is a nullipara with a history of fertility treatment. She presented with bilateral ovarian cysts suspected to be malignant and an elevated CA-125 level. Intraoperative frozen section showed borderline ovarian tumor, allowing for conservative management. Mrs. A, 32-years old, with right cystic ovarian neoplasm suspected to be malignant and elevated CA-125. Frozen section showed results of cystadenocarcinoma, patient's family was informed of the result during the surgery and the operator continued to manage the patient conservatively. Ms. N, 27 years old, was referred with suspected ovarian malignancy and the differential diagnosis of peritoneal tuberculosis. Frozen section confirmed the presence of tuberculosis infection, and the patient was managed accordingly. Conclusion: Despite conservative management being top priority treatment in young-aged women with ovarian neoplasm, additional information of frozen section allows for more accurate management.